Floppy iris syndrome associated with specific medication intake: A narrative review - Maluskova, Miroslava; Vidlar, Ales; Maresova, Klara; Lounova, Veronika; Karhanova, Marta (Biomedical papers, 2023)
Intraoperative floppy iris syndrome (IFIS) is a cataract surgery complication that remains a challenge for eye surgeons. It is caused by the antagonism of alfa-1-adrenergic receptors within the dilator muscle of the iris, thus preventing the iris from dilation during a cataract surgery. The long-term blocking alfa-1 adrenergic receptors by the chronic use of a number of systemic medications may lead to permanent anatomical atrophy of the dilator muscle of the iris. The most common drugs associated with the development of IFIS are tamsulosin and other alpha-1 adrenergic receptor antagonists prescribed to patients with low urinary tract symptoms (LUTS). There are other systemic medications that have been reported to have increased risk for IFIS. It is crucial for the ophthalmologist to identify the high-risk patients prone to develop IFIS. Its presence may complicate the course of cataract surgery, ultimately negatively affecting visual outcome. Cataract surgery should be performed by an experienced eye surgeon using alternative pharmacological and surgical techniques. Interdisciplinary cooperation is essential to mitigate potential complications. Patients should be informed by their physicians about the need to report a medication history to their eye specialists, especially before cataract surgery.
Keywords: intraoperative floppy iris syndrome; lower urinary tract symptoms; alpha-blockers; tamsulosin; iris